Molecular mechanisms of mitochondrial DNA release and activation of the cGAS-STING pathway - Kim, Jeonghan; Kim, Ho-Shik; Chung, Jay H. (Experimental & molecular medicine, 2023)
In addition to constituting the genetic material of an organism, DNA is a tracer for the recognition of foreign pathogens and a trigger of the innate immune system. cGAS functions as a sensor of double-stranded DNA fragments and initiates an immune response via the adaptor protein STING. The cGAS-STING pathway not only defends cells against various DNA-containing pathogens but also modulates many pathological processes caused by the immune response to the ectopic localization of self-DNA, such as cytosolic mitochondrial DNA (mtDNA) and extranuclear chromatin. In addition, macrophages can cause inflammation by forming a class of protein complexes called inflammasomes, and the activation of the NLRP3 inflammasome requires the release of oxidized mtDNA. In innate immunity related to inflammasomes, mtDNA release is mediated by macropores that are formed on the outer membrane of mitochondria via VDAC oligomerization. These macropores are specifically formed in response to mitochondrial stress and tissue damage, and the inhibition of VDAC oligomerization mitigates this inflammatory response. The rapidly expanding area of research on the mechanisms by which mtDNA is released and triggers inflammation has revealed new treatment strategies not only for inflammation but also, surprisingly, for neurodegenerative diseases such as amyotrophic lateral sclerosis. Inflammatory diseases: Understanding mitochondrial DNA release Cytosolic DNA activates the cGAS-STING pathway which mediates inflammation and antiviral response. One source of cytosolic DNA is ‘self ‘ DNA, such as mitochondrial DNA. Studies of how mitochondria can release DNA and trigger dangerous immune responses are revealing potential treatments for inflammatory diseases. Cells isolate DNA in their nuclei and mitochondria, but if this ‘self-DNA’ leaks out, it triggers the same immune responses that the body uses to fight DNA from viruses or bacteria. Jeonghan Kim at The Catholic University of Korea College of Medicine in Seoul, South Korea, and co-workers reviewed research into the mechanism causing mitochondrial DNA release, and the resulting inflammatory pathways. Although cGAS-STING is the central driver of such inflammation, treatments targeting it may also suppress the body’s antimicrobial immunity. A safer alternative maybe to inhibit mitochondrial VDAC oligomerization, which releases mitochondrial DNA.